Automated Real-Time Vision Quality Inspection Monitoring System - N.N.S. Abdul Rahman; N.M. Saad; A.R. Abdullah; M.R.M. Hassan; M.S.S.M Basir; N.S.M. Noor (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
The requirement of product quality inspection in industries for product standardized leads to a development of the quality inspection system. The problem is related to a manual inspection that is done by a human as an inspector. This paper presents an automated real-time vision quality inspection monitoring system as a problem solver to a manual inspection that is tedious and time-consuming task as well as reducing cost especially in small and medium enterprise industries (SME). For the proposed system, soft drink is used as the test product for quality inspection. The system uses computer-network to inspect two quality inspections which are color concentration and water level. The analysis includes pre-processing, color concentration using the histogram and quadratic distance and level inspection using coordinate vertical and horizontal reference levels. The similarities of both experimental and simulation results are obtained for both parameters which are 100% accuracy using 205 samples.